Asymmetric Cell Division and Template DNA Co-Segregation in Cancer Stem Cells - Pine, Sharon R.; Liu, Wenyu (Frontiers in Oncology, 2014)
During tissue homeostasis, normal stem cells self-renew and repopulate the diverse cell types found within the tissue via a series of carefully controlled symmetric and asymmetric cell divisions. The notion that solid tumors comprise a subset of cancer stem cells with dysregulated self-renewal and excessive symmetric cell divisions has led to numerous studies aimed to elucidate the mechanisms regulating asymmetric cell division under steady-state conditions, during stem cell expansion, and in cancer. In this perspective, we focus on a type of asymmetry that can be established during asymmetric cell division, called non-random co-segregation of template DNA, which has been identified across numerous species, cell types and cancers. We discuss the role of p53 loss in maintaining self-renewal in both normal and malignant cells. We then review our current knowledge of the mechanisms underlying co-segregation of template DNA strands and the stem cell pathways associated with it in normal and cancer stem cells.